Coping and Caring: Support Resources Integral to Perioperative Nurses during the Process of Organ Procurement Surgery - Smith, Zaneta; Leslie, Gavin; Wynaden, Dianne (Wiley-Blackwell Publishing, 2016)
Aim and Objective: This paper, discusses and explores the levels of support provided to perioperative nurses' when participating in multi-organ procurement surgery and the impact to their overall well-being. Background: Assisting within multi-organ procurement surgical procedures has been recognised to impact on the well-being of perioperative nurses leaving little opportunity for them to recover from their participation or to seek available support resources. To date, this area has remained largely unexplored with limited evidence of how nurses manage and cope with these procedures, in addition to the support received in the workplace. Design: A qualitative grounded theory method. Methods: The study was informed by perioperative nurses (n=35) who had previous participatory experience in these surgical procedures from two Australian states. Theoretical sampling directed the collection of data via semi structured in-depth interviews. Data were analysed using the constant comparative method. Results: Three components of levels of support were identified from the data; lacking support within the operating room organisation; surgical team support and access to external professional support. Conclusion: These findings offer new insights into how nurses manage and cope with their participation in organ procurement surgical procedures and what types of support resources can be seen as barriers or enablers to their overall experiences. The need for timely and adequate support is vital to their overall well-being and future participation in organ procurement surgery. These findings have the potential to guide further research with implications for clinical initiatives and practices, looking at new ways of supporting perioperative nurses within the clinical environment both locally and internationally. Relevance to clinical Practice: Healthcare organisations need to acknowledge the emotional, psychosocial and psychological health and well-being of nurses' impacted by these surgical procedures and provide appropriate and timely clinical support within the work environment.